The Influence Of Leadership, Motivation And Communication On Employee Performance In Agency Regional Development Planning South Tangerang City - Novaryansah, N.; Suwanti, S. (Golden Ratio of Human Resource Management, 2021)
This research was conducted with the aim of: (1) To analyze the influence of leadership on employee performance at the Regional Development Planning Board of South Sulawesi Province; (2) To analyze the effect of motivation on employee performance at the Regional Development Planning Board of South Sulawesi Province; (3) To analyze the effect of communication on employee performance at the Regional Development Planning Board of South Sulawesi Province. This study uses primary data through a survey of 59 employees as a sample of the total number of employees of 143 employees with a minimum working period of 1 year as of December 2018, the survey was conducted from April to May 2019. The data was processed and analyzed using Statistical Packages for Social Science (SPSS) 20. The results of this study indicate that: (1) leadership has a positive and significant influence on the performance of employees at the Regional Development Planning Agency of South Sulawesi Province; (2) motivation has a positive and significant influence on employee performance at the Regional Development Planning Board of South Sulawesi Province; (3) communication has a positive and significant influence on employee performance at the Regional Development Planning Agency of South Sulawesi Province. This means that effective leadership has a positive impact on employees. The leader must play his function as a function of instruction, consultation, participation, delegation and control. Create high work motivation and multi-way communication will impact on improving employee performance.